Earnings quality in UK high tech firms - TER, Fook Ten (2016)
This paper examines the earnings quality of UK high tech firms. Results reveal lower multiplier for earnings and higher multiplier for book value of equity for high tech firms as compared to traditional firms. In addition, high tech firms have lower incremental explanatory power of earnings and higher incremental explanatory power of book value of equity compared to traditional firms. Besides, high tech firms have lower persistence of earnings as indicated by its lower estimated coefficient of lagged earnings and weaker explanatory power of the model. Surprisingly, traditional firms have higher magnitude of total accruals while high tech firms have higher higher magnitude of discretionary accruals. All in all, these results show low earnings quality in UK high tech firms, suggested by low value relevance of earnings and lower earnings persistency. However, despite lower earnings quality, stock market is able to predict high tech firms’ stock price with greater accuracy using information regarding book value of equity and earnings. For this matter, the findings in this paper contradicts the claim of lower value relevance of traditional financial information for high tech firms.